Economics for cambridge international AS & A level coursebook - Bamford, Colin (New York ; Cambridge University Press, 2021)
"This series supports teachers and learners of Cambridge International AS & A Level Economics (9708). Introduce your learners to the world of economics with the fourth edition of our Cambridge International AS & A Level Economics series. Featuring a coursebook with digital access, digital coursebook, workbook with digital access and digital teacher's resource, your students will gain a clear understanding of how economics operates on an international scale, while developing key skills, such as analysis and evaluation"
AS & A level
Keywords: Economics